Bromatologic study of artisanal formulae and a proposal of ambulatory protocol of nutritional enteral care: DOI: 10.15343/0104-7809.20094467479 - Alberto Nunes Cirqueira; Fabiana Poltronieri; Deise Caramico; Vera Silvia Frangella (O Mundo da Saúde)
Enteral nutrition (EN) is an important therapeutic tool for individuals with complete gastrointestinal treatment, but able to ingest nutrients in adequate amount and/or quality. Thus, its formulas must follow nutritional recommendations and have its cost and chemical composition identified. The implementation of a care protocol guarantees EN qualification. The study aims to determine cost and chemical composition of 4 formularizations (F1 - F4) comparing them with F5 and F6 published by Araújo; Menezes (2005) and to propose a protocol for nutritional care of this population. The analyzed formularizations are composed by in natura industrial foods, and are evaluated as regards cost and nutritional composition through bromatologic laboratorial techniques for determination of the centesimal composition and Prosky et al. (1988) as concerns staple fibers. The protocol was based on the literature and current legislation. F1 was less expensive without reaching lipidic recommendations; F2 had low proteic and caloric values and F3 reached nutritional values, but is more expensive. F4 reached recommended nutritional values (0.8 Kcal/ml; 15% protein, 23% of lipids and 62% of carbohydrates) with reduced cost (R$331,20/month), higher only than F1’s. F1 presented 7,2 g of TP (Total Fiber content) (47.2% insoluble content (FI) and 52.8% soluble content (FS)); F2: 2.4g of FT (83.3% FI and 16.7% FS); F3: 7.6 g of FT (52.6% FI and 47.4% FS) and F4: 5.6g of FT (89.3% FI and 10.7% FS), confirming the inadequacy of staple fibers in these diets. The protocol combines nutritional variables (nutritional evaluation, food anamneses) and clinic (diagnostic, pharmacotherapy, examinations) regarding adequacy of individualized nutritional care (type, volume, administration of the formula). The best cost / benefit relation was that of F4, reaching nutritional balance, being an alternative for home feeding for individuals lacking income. The results of staple fibers ratify the necessity of its supplementation when EN is exclusive. The protocol favors: register, control and evaluation of EN effectiveness.